Humulus lupulus Promoting Osteoblast Activity and Bone Integrity: Effects and Mechanisms - Wanionok, Nahuel Ezequiel (2025)
Osteoporosis is characterized by an imbalance between bone formation and resorption, leading to decreased bone mass and an increased fracture risk, mainly associated with aging. Current treatments include anti-resorptive and anabolic drugs. However, these often have side effects, leadingmany patients to seek natural biological alternatives. We have demonstrated previously that hops extract, rich in compounds with estrogenic activity classified as phytoestrogens, exerts osteogenic effects by promoting the osteoblastic differentiation of bone marrowstemcells (BMSCs)while inhibiting osteoclast activity in vitro. In our study, youngmale Sprague Dawley rats were randomized into two groups: one received hops extract (LPL, 1% w/v in drinking water) for two months, and the other drank water alone (C). The rats were euthanized, and their femurs were dissected and processed for static histomorphometry and bone biomechanics. Additionally, BMSCs were isolated from the humeri to evaluate their osteogenic potential. Our result demonstrated that LPL treatment enhanced the osteogenic potential of humeral BMSCs in ex vivo assays, upregulating osteogenic genes and downregulating proresorptivemarkers. These findings correlated with improved femoral bonemicroarchitecture and biomechanical parameters. In conclusion, a two-month treatment with LPL enhanced the osteogenic capacity of BMSCs, improving bonemicroarchitecture and biomechanical properties. These results suggest its potential as a natural alternative for promoting bone health.